(untitled) - Kirk, Guy (New York, 2004)
Submerged soils and the wetlands they support are of huge practical importance: in global element cycles, as centres of biodiversity, in global food production. They are also uniquely interesting scientifically because of their peculiar biogeochemistry and the adaptations of plants and microbes to it. This book describes the physical, chemical and biological processes operating in submerged soils and governing their properties. It describes the transport processes controlling the fluxes of gases and solutes through the soil; the interchange of solutes between solid, liquid and gas phases; reduction and oxidation processes; biological processes in the soil and overlying water; and processes in the roots and rhizospheres of wetland plants. The dynamics of nutrients, toxins, pollutants and trace gases are then discussed in terms of these processes and in relation to wetland productivity and global element cycles. Written by a renowned expert in the field, this work will be invaluable to earth, environmental and agricultural scientists concerned with natural or man-made wetlands, and to advanced undergraduate and graduate studen ts of these topics.
Sinh thái đất ngập nước
Keywords: Hydromorphic soils,Soil chemistry,Biogeochemistry